Presentation of the content network of HSE systematic management components and operational plan in the Arbaeen procession - Minoo Safipour; Mojgan Zaeimdar; Manouchehr Omidvari; Razi Naserifar (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  The Arbaeen pilgrimage in Iraq, one of the world's largest religious gatherings, presents unique challenges in health, safety, and environmental management. Issues like overcrowding, poor access to medical care, insufficient sanitation, and communicable diseases threaten pilgrims' well-being. Past incidents and vulnerable groups like the elderly and children intensify risks. A comprehensive HSE management model using a thematic framework and the PDCA cycle is needed to enhance safety, resilience, and environmental sustainability. This study aims to propose a comprehensive model for HSE management. Materials & Methods: The study, conducted in three Iranian cities from April to October 2023, involved seven experts from various fields, including HSE managers, public health professionals, crisis response specialists, and NGO coordinators. Data was collected using literature review, semi-structured interviews, and a Delphi-based questionnaire. Thematic analysis was performed using the Attride-Stirling network model. Data were analyzed using SPSS V25, and descriptive statistics (mean, SD) were calculated. The threshold for statistical significance was set at P < 0.05. Results: Findings identified four key domains: risk and crisis management, public health and hygiene, resource provision, and education and governance. These were structured into an operational plan based on the PDCA model. Conclusion: The study presents a comprehensive HSE management model for mass religious gatherings, specifically designed for the Arbaeen pilgrimage. It integrates thematic network analysis and the PDCA planning framework, emphasizing proactive planning to reduce risks, enhance public health services, and manage environmental impacts. Future research should incorporate real-time monitoring technologies and validate them in different cultural settings.